The effect of the ergometer design on pelvic twist and lowerback flexion in elite rowers - Fohanno, V.; Nordez, A.; Smith, R.; Colloud, F. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
Pelvic twist and lower-back flexion are considered as two important risk factors regarding lower-back injuries in rowers training frequently on ergometers. Mobile ergometers could be helpful because their design decreases the inertial loads that the rower has to overcome at the catch. Hence, the purpose of this study was to investigate pelvic twist and lower-back flexion with respect to the ergometer design. These two kinematic parameters were examined on ten elite rowers during one stationary and two mobile ergometer sessions performed at 20 strokes per minutes. The differences related to pelvic twist and lower-back flexion were very small. These findings suggested that further studies should be performed at higher paces and focused on the whole trunk motion and muscle activity to offer an overview of the influence of the ergometer design.